'Half the world away': Cultural distance and intertextual incompetence in the American reception of British TV comedy. Issue 1 (1st March 2020) - Diffrient, David Scott
Comedy has long been thought of as a genre that does not 'travel' well, owing to the fact that humour is often tied to culturally specific (or 'local') references that might be lost on audiences outside a text's originating context. In recent years, however, a few globally recognized comedians, such as Simon Pegg, have suggested that the jokes that pepper British comedies can be easily understood by non-British audiences. This article critically interrogates both premises and questions whether the intertextual incompetence of viewers might exacerbate feelings of literal and figurative distance while solidifying an insider/outsider binary that resembles the inclusionary and exclusionary rhetoric at the heart of nationalistic discourse. Drawing upon the insights of comedy and language theorists, the author adopts an autoethnographic approach that foregrounds his own (frequently failed) attempts to disentangle culturally specific references in British sitcoms. Such an approach reveals how, to varying degrees, class, distinction and the cultural capital or taste presumably needed to discern the value and meaning of something all impinge on the connective yet distancing act of transnational TV spectatorship.